"We believe in you, like really believe in you": Initiating a realist study of (re)engagement initiatives for youth not in employment, education or training with experiences from northern Sweden. (December 2020) - Jonsson, Frida; Goicolea, Isabel
Highlights: (Re)engagement initiatives are expected to facilitate integration of "NEET" youth. The youths' wellbeing may improve through the provision of activities and support. Holistic and flexible services might help the youth gain confidence and competences. Generative mechanisms might be triggered in a caring and collaborative context. Abstract: Due to a scarcity of rigorous evaluations and to commence a realist study addressing the lack of knowledge about the workings of interventions directed towards "NEET" youth, this research aimed to understand how and under what circumstances (re)engagement initiatives are expected to facilitate the social integration of young people who are in a situation that prevents them from entering into studies or work. By conducting the first phase in realist evaluation, qualitative interviews with five managerial stakeholders from two northern Swedish initiatives and reviews of documents were carried out for data collection. Using thematic analysis and retroductive reasoning, an intervention-context-actors-mechanisms-outcomes configuration was developed to elicit an initial programme theory that explained how the initiatives were presumed to operate and under what contextual contingencies. The results indicate that the intervention is expected to improve the youths' wellbeing and engage them in work or studies by strengthening their competence and confidence in a caring and collaborative context. To incorporate the diverse voices and heterogeneous experiences of youth themselves, and ascertain whether the intervention works as intended, for whom, in what conditions and why, the results now need to be tested in selected cases and refined in subsequent phases of evaluation research.